2021
DOI: 10.1088/1742-6596/1882/1/012134
|View full text |Cite
|
Sign up to set email alerts
|

Security and privacy awareness of smartphone users in Indonesia

Abstract: The number of smartphone users in Indonesia is increasing every year and has been growing rapidly since Covid-19 hit Indonesia. Smartphones store a lot of personal and information data, such as photos, videos, contact lists, e-mails to social media accounts. A large amount of personal data on smartphones causes an increasing number of threats to information security and privacy. This study aims to measure the knowledge and level of awareness of smartphone users in Indonesia on information security and privacy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Some studies have also concluded that although younger users have a higher level of security than older users [35], there are still young users who can be quite vulnerable, because they do not know how to increase security either in general, such as using privacy settings [36], or setting strong password combinations [37]. Indonesia has a low level of security awareness amongst smartphone users, such as the results of storing important data on smartphones and installing illegal applications into them [38]. Throughout all these studies, it has been noted that there is no previous research that analyzes the level of personal data security awareness amongst higher education students (largest age group of social media users) in Indonesia.…”
Section: Factors Influencing Personal Data Security Awarenessmentioning
confidence: 99%
“…Some studies have also concluded that although younger users have a higher level of security than older users [35], there are still young users who can be quite vulnerable, because they do not know how to increase security either in general, such as using privacy settings [36], or setting strong password combinations [37]. Indonesia has a low level of security awareness amongst smartphone users, such as the results of storing important data on smartphones and installing illegal applications into them [38]. Throughout all these studies, it has been noted that there is no previous research that analyzes the level of personal data security awareness amongst higher education students (largest age group of social media users) in Indonesia.…”
Section: Factors Influencing Personal Data Security Awarenessmentioning
confidence: 99%
“…The findings obtained from 204 participant shows that most users are aware of some security practice such as using suitable screen lock settings to safeguard against unauthorized access. The measure of the knowledge and level of security awareness of Smartphone users in Indonesia on information security and privacy was also conducted [22]. The results show a low awareness level in terms of threats and attacks.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…In ( 1) and ( 2) show the calculation of the value input gate and possible value from the cell state. RNN concept can be described as a formula, as in (1). In that equation 𝑥 𝑡 is hidden state from input of time-t and ℎ 𝑡−1 is hidden state in previous time.…”
Section: Rnn-lstmmentioning
confidence: 99%
“…Almost 197 million people in Indonesia have used the internet in their daily life. This figure is directly proportional to the increase in social media users in Indonesia [1]. Indonesian society uses social media to publish their views and opinions under various circumstances [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation